Preparation method of nano laminated thermal expansion vermiculite paper
By designing thermally expanded vermiculite paper with nano-laminated structures in thermal battery materials, the problems of traditional materials aging and insufficient flexibility in high-temperature environments are solved, and efficient heat insulation and high-temperature resistance are achieved, suitable for weapons and equipment and aerospace field.
Patent Information
- Application Number
- CN202411420268.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-07
AI Technical Summary
Existing thermal battery materials are prone to aging in high temperature environments, large in size, heavy in mass and difficult to flexibly wrap. Traditional thermal insulation materials perform poorly in high temperature resistance and flexible properties, limiting their application in weapons and equipment and aerospace fields.
By designing the thermally expanded vermiculite paper with a nano-laminated structure, the chemical reaction of oxalic acid powder and thermally expanded vermiculite powder is peeled into nanosheet paste and processed at high temperature to increase the layer spacing and air gap, improving thermal insulation performance and flexibility.
The prepared nano-laminated thermally expanded vermiculite paper has high expansion rate, good flexibility and thermal insulation properties, and is suitable for use in high-temperature environments and is suitable for weapons and equipment and aerospace fields.
Smart Images

Figure CN119266029A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano material preparation, in particular to a method for preparing nano laminated thermal expansion vermiculite paper. Background Art
[0002] The operating temperature of thermal batteries inside nuclear missiles, guided missiles, torpedoes, and artillery is above 500°C, and the instantaneous temperature is as high as 1000°C. There is an urgent need for flexible, high-temperature resistant, and efficient thermal insulation materials to wrap and encapsulate thermal batteries to reduce heat loss, extend the thermal life of thermal batteries, and improve the utilization rate of electrode materials. Although traditional thermal insulation materials such as glass wool and rock wool have certain thermal insulation effects, they still have problems such as large size, heavy weight, easy aging and performance degradation after long-term use.
[0003] Vermiculite, as a natural layered silicate mineral, performs well in fire resistance and heat insulation. After high-temperature roasting, the volume of raw vermiculite flakes can rapidly expand up to more than 30 times. The expanded vermiculite looks like leeches and is called thermal expansion vermiculite. Although thermal expansion vermiculite has been used as one of the thermal insulation materials, the common products on the market are mainly in the form of plates or powders, which are not conducive to reassembly and winding. In recent years, a large number of researchers have used the cation exchange properties of thermal expansion vermiculite to chemically intercalate it to obtain single-layer or few-layer vermiculite nanosheets, which are then formed into vermiculite paper by methods such as filtration, evaporation induction or polymer co-assembly to meet the needs of specific applications. Although the prepared vermiculite paper has high mechanical properties, its structure is dense, and its flexibility and heat resistance need to be improved. In addition, the preparation process often involves complex chemical treatment steps, and it is difficult to prepare on a large scale, which limits production efficiency and commercial application scope. Therefore, it is urgent to develop a flexible, high-temperature resistant and highly thermally insulating nano-laminated vermiculite paper, and at the same time explore the corresponding economical and effective preparation method suitable for large-scale production to meet the needs of key fields such as weapons and equipment, aerospace, etc. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing nano-laminated heat-expandable vermiculite paper, design and prepare nano-laminated heat-expandable vermiculite paper with a nano-laminated structure to achieve flexibility and high temperature resistance integration, by regulating the topological structure of vermiculite nanosheets from a planar shape to a folded shape (such as Figure 1 As shown in the figure), on the one hand, the size of the nano-building unit is hidden to reserve space for the deformation of the thermal expansion vermiculite paper, and on the other hand, nano-scale gaps are constructed to improve the thermal insulation of the thermal expansion vermiculite paper, providing technical support for the development of flexible, high temperature resistant and high thermal insulation integrated materials for weapon equipment and aerospace.
[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0006] A method for preparing nano-laminated thermal expansion vermiculite paper comprises the following steps:
[0007] Step S1: weighing the following raw materials according to mass fractions: 0.1-1 parts of oxalic acid powder, 1-2 parts of heat-expanded vermiculite powder, 5-10 parts of deionized water, and 5-30 parts of micron-sized ceramic balls; Step S2: dissolving the oxalic acid powder and the heat-expanded vermiculite powder in deionized water, and mixing to obtain a heat-expanded vermiculite suspension;
[0008] Step S3: adding micron-sized ceramic balls to the heat-expanded vermiculite suspension obtained in step S2, and then stirring for 6-10 hours, wherein the micron-sized ceramic balls shear the heat-expanded vermiculite and drive the vermiculite particles in the heat-expanded vermiculite to shear and rub against each other, thereby peeling the vermiculite nanosheets from the surface of the vermiculite particles to obtain a vermiculite nanosheet paste;
[0009] Step S4: pouring the vermiculite nanosheet paste obtained in step S3 into a circular polytetrafluoroethylene mold and fully drying it to obtain a vermiculite film;
[0010] Step S5: treating the vermiculite film obtained in step S4 at high temperature, the oxalic acid molecules between the vermiculite nanosheets are instantly decomposed into gas, and the water molecules between the vermiculite nanosheets are instantly vaporized, and the vermiculite film expands to obtain thermal expansion vermiculite paper.
[0011] Furthermore, in step S1, the bulk density of the heat-expanded vermiculite powder is 0.07-0.29 g / cm 3 The micron-sized ceramic balls include zirconium oxide, aluminum oxide or silicon nitride micron-sized balls, and the diameter of the micron-sized ceramic balls is 200-800 μm.
[0012] Furthermore, in step S3, the stirring linear speed is 10 m / s-25 m / s, the thickness of the vermiculite nanosheets is less than 5 nm, the size of the vermiculite nanosheets is 50-800 μm, and the viscosity of the vermiculite nanosheet paste is 300-600 Pa·s.
[0013] Furthermore, in step S4, the drying temperature is 50-80° C., the drying time is 2-5 hours, and the thickness of the vermiculite film is 5-20 μm.
[0014] Furthermore, in step S5, the high temperature treatment temperature is 300-600° C., and the treatment time is 2-10 min.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] 1. In order to obtain vermiculite nanosheet paste, the heat-expanded vermiculite powder is firstly peeled off by sand grinding. During the peeling process, oxalic acid molecules enter the interlayer of vermiculite, increasing the interlayer spacing of vermiculite nanosheets, which helps to improve the peeling efficiency;
[0017] 2. In the step of drying the vermiculite nanosheet paste into a film, since the vermiculite nanosheets have a high specific surface area and adjacent vermiculite nanosheets have the same charge, an electrostatic repulsion is formed, and a blocked grid is formed between the vermiculite nanosheets, showing a high viscosity, which is conducive to the casting of the vermiculite nanosheets into a film;
[0018] 3. The vermiculite film is heat treated at high temperature to obtain heat-expanded vermiculite paper. During the heat treatment process, the oxalic acid molecules between the vermiculite nanosheets are instantly decomposed into gas, and the molecules between the vermiculite nanosheets are instantly vaporized, which increases the expansion degree of the vermiculite film and increases the wrinkles and air gaps of the vermiculite nanosheets, which is conducive to improving the flexibility and thermal insulation performance of the vermiculite paper;
[0019] 4. Using the two-dimensional layered structure of vermiculite, the heat-expanded vermiculite is first peeled off into two-dimensional nanostructure units, and then assembled into a film. After the film is formed, there is a weak force between the vermiculite nanosheets. Subsequently, a gas generating agent is introduced between the vermiculite nanosheets, and the expandable characteristics of vermiculite are used to prepare a nano-laminated heat-expanded vermiculite paper with a high expansion rate. The prepared heat-expanded vermiculite paper has more air gaps, which is beneficial for thermal insulation. At the same time, the surface wrinkles caused by the expansion of the vermiculite nanosheets reserve space for paper deformation, showing good flexibility.
[0020] 5. The heat-expanded vermiculite paper prepared by the present invention can be used as a new type of wrapping paper. Its application is not limited to a specific traditional field, but has wide application value in the fields of gas barrier, heat insulation and flame retardancy, and electrical insulation. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the conformational transformation of the vermiculite nanosheets of the present invention;
[0022] Figure 2 is an AFM image of the vermiculite nanosheets of the present invention;
[0023] Figure 3 is a SEM image of a cross section of the vermiculite membrane of the present invention;
[0024] Figure 4 is a schematic diagram of the vermiculite membrane of the present invention;
[0025] Figure 5 is a SEM image of the surface of the vermiculite film of the present invention;
[0026] Figure 6 is a stress-strain curve diagram of the vermiculite membrane of the present invention;
[0027] Figure 7 is a SEM image of a cross section of the heat-expanded vermiculite paper of the present invention;
[0028] Figure 8is a SEM image of the surface of the heat-expanded vermiculite paper of the present invention;
[0029] Fig. 9 It is the stress-strain curve diagram of the heat-expanded vermiculite paper of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Embodiment 1:
[0032] A method for preparing nano-laminated thermal expansion vermiculite paper comprises the following steps:
[0033] Step S1: Weigh the following raw materials according to mass fraction: 10 g oxalic acid powder, bulk density 0.12 g / cm 3 20g of heat-expanded vermiculite powder, 100g of deionized water, and 300g of zirconia balls with a diameter of 600μm; Step S2: dissolving oxalic acid powder and heat-expanded vermiculite powder in deionized water, and putting them into a stainless steel tank and mixing them evenly to obtain a heat-expanded vermiculite suspension;
[0034] Step S3: adding zirconium oxide balls to the heat-expanded vermiculite suspension obtained in step S2, and then stirring at a linear speed of 20 m / s for 8 h, wherein the zirconium oxide balls shear the heat-expanded vermiculite and simultaneously drive the hot vermiculite particles in the heat-expanded vermiculite to shear and rub against each other, thereby peeling the vermiculite nanosheets from the surface of the vermiculite particles to obtain a vermiculite nanosheet paste, and separating the zirconium oxide balls with a 50-mesh filter screen under vacuum assistance to obtain a yellowish vermiculite nanosheet paste, wherein the vermiculite nanosheets in the vermiculite nanosheet paste have a size of 50-800 nm, and a thickness of about 2 nm (e.g., Figure 2 shown);
[0035] Step S4: pour the vermiculite nanosheet paste obtained in step S3 into a circular polytetrafluoroethylene mold and dry it at 60°C for 3h to obtain a vermiculite film. The vermiculite nanosheets in the vermiculite film are arranged in an orderly manner and have a dense structure. The thickness of the vermiculite film is 8.5 μm (e.g. Figure 3 As shown in the figure), the surface of the vermiculite film is smooth and flat (as shown in the figure). Figure 4 and Figure 5 As shown in the figure), the mechanical properties of the vermiculite membrane were tested using a GB / T16491-2008 electronic universal testing machine. The tensile strain of the vermiculite membrane was 1.7% and the toughness was 1.45 MJ / m 3, the tensile strength is 15.8MPa, and the stress-strain curve of the vermiculite membrane is obtained (such as Figure 6 shown);
[0036] Step S5: The vermiculite film obtained in step S4 is treated at 400°C for 5 minutes, and the oxalic acid molecules between the vermiculite nanosheets are instantly decomposed into gas, and the water molecules between the vermiculite nanosheets are instantly vaporized, and the vermiculite film expands to obtain thermal expansion vermiculite paper. The thickness of the thermal expansion vermiculite paper is 100 μm, which is expanded by about 12 times, and the interlayer spacing is large (such as Figure 7 As shown in the figure, the surface of the heat-expanded vermiculite paper has a lot of wrinkles (such as Figure 8 As shown in the figure), the mechanical properties of the heat-expanded vermiculite paper were tested using a GB / T16491-2008 electronic universal testing machine. The tensile strain of the heat-expanded vermiculite paper was 6.1% and the toughness was 3.6 MJ / m 3 , the tensile strength is 11.5MPa, and the stress-strain curve of vermiculite paper is obtained (such as Fig. 9 as shown).
[0037] Embodiment 2:
[0038] A method for preparing nano-laminated thermal expansion vermiculite paper comprises the following steps:
[0039] Step S1: Weigh the following raw materials according to mass fraction: 10 g oxalic acid powder, bulk density 0.12 g / cm 3 20g of heat-expanded vermiculite powder, 100g of deionized water, and 300g of zirconia balls with a diameter of 200μm; Step S2: dissolving oxalic acid powder and heat-expanded vermiculite powder in deionized water, and putting them into a stainless steel tank and mixing them evenly to obtain a heat-expanded vermiculite suspension;
[0040] Step S3: adding zirconium oxide balls to the heat-expanded vermiculite suspension obtained in step S2, and then stirring at a linear speed of 25 m / s for 8 hours, wherein the zirconium oxide balls shear the heat-expanded vermiculite and simultaneously drive the hot vermiculite particles in the heat-expanded vermiculite to shear and rub against each other, thereby peeling off the vermiculite nanosheets from the surfaces of the vermiculite particles to obtain a vermiculite nanosheet paste, and separating the zirconium oxide balls with an 80-mesh filter screen under vacuum assistance to obtain a yellowish vermiculite nanosheet paste, wherein the vermiculite nanosheets in the vermiculite nanosheet paste have a size of 50-800 nm and a thickness of about 1.1 nm;
[0041] Step S4: pouring the vermiculite nanosheet paste obtained in step S3 into a circular polytetrafluoroethylene mold, and drying at a temperature of 50° C. for 3 h to obtain a vermiculite film. The vermiculite nanosheets in the vermiculite film are orderly arranged and have a compact structure. The thickness of the vermiculite film is 6 μm, and the surface of the vermiculite film is smooth and flat. The mechanical properties of the vermiculite film are tested using a GB / T16491-2008 electronic universal testing machine, and the tensile strain of the vermiculite film is measured to be 2.1%, and the toughness is 1.9 MJ / m 3 , tensile strength is 14.2MPa;
[0042] Step S5: treating the vermiculite film obtained in step S4 at 300° C. for 10 min, the oxalic acid molecules between the vermiculite nanosheets are instantly decomposed into gas, and the water molecules between the vermiculite nanosheets are instantly vaporized, and the vermiculite film expands to obtain heat-expanded vermiculite paper. The thickness of the heat-expanded vermiculite paper is 80 μm, which is expanded by about 13 times, and the interlayer spacing is large. The surface of the heat-expanded vermiculite paper has a large number of wrinkles. The mechanical properties of the heat-expanded vermiculite paper are tested using a GB / T16491-2008 electronic universal testing machine, and the tensile strain of the heat-expanded vermiculite paper is measured to be 7.9%, and the toughness is 5.4 MJ / m 3 , tensile strength is 10.1MPa.
[0043] Embodiment three:
[0044] A method for preparing nano-laminated thermal expansion vermiculite paper comprises the following steps:
[0045] Step S1: Weigh the following raw materials according to mass fraction: 10 g oxalic acid powder, bulk density 0.12 g / cm 3 20g of heat-expanded vermiculite powder, 100g of deionized water, and 300g of zirconia balls with a diameter of 800μm; Step S2: dissolving oxalic acid powder and heat-expanded vermiculite powder in deionized water, and putting them into a stainless steel tank and mixing them evenly to obtain a heat-expanded vermiculite suspension;
[0046] Step S3: adding zirconium oxide balls to the heat-expanded vermiculite suspension obtained in step S2, and then stirring at a linear speed of 10 m / s for 8 hours, wherein the zirconium oxide balls shear the heat-expanded vermiculite and simultaneously drive the hot vermiculite particles in the heat-expanded vermiculite to shear and rub against each other, thereby peeling the vermiculite nanosheets from the surfaces of the vermiculite particles to obtain a vermiculite nanosheet paste, and separating the zirconium oxide balls with an 80-mesh filter screen under vacuum assistance to obtain a yellowish vermiculite nanosheet paste, wherein the vermiculite nanosheets in the vermiculite nanosheet paste have a size of 50-800 nm and a thickness of about 3.2 nm;
[0047] Step S4: pouring the vermiculite nanosheet paste obtained in step S3 into a circular polytetrafluoroethylene mold, and drying at a temperature of 80° C. for 3 h to obtain a vermiculite film. The vermiculite nanosheets in the vermiculite film are arranged in an orderly manner and have a compact structure. The thickness of the vermiculite film is 12 μm, and the surface of the vermiculite film is smooth and flat. The mechanical properties of the vermiculite film are tested using a GB / T16491-2008 electronic universal testing machine, and the tensile strain of the vermiculite film is measured to be 1.1%, and the toughness is 0.9 MJ / m 3 , tensile strength is 17.3MPa;
[0048] Step S5: treating the vermiculite film obtained in step S4 at 600° C. for 2 min, the oxalic acid molecules between the vermiculite nanosheets are instantly decomposed into gas, and the water molecules between the vermiculite nanosheets are instantly vaporized, and the vermiculite film expands to obtain heat-expanded vermiculite paper. The thickness of the heat-expanded vermiculite paper is 145 μm, which is expanded by about 12 times, and the interlayer spacing is large. The surface of the heat-expanded vermiculite paper has a large number of wrinkles. The mechanical properties of the heat-expanded vermiculite paper are tested using a GB / T16491-2008 electronic universal testing machine, and the tensile strain of the heat-expanded vermiculite paper is measured to be 4.2%, and the toughness is 1.9 MJ / m 3 , tensile strength is 13.2MPa.
[0049] By comparing the preparation methods of a nano-laminated heat-expandable vermiculite paper in Example 1, Example 2 and Example 3, the following table is obtained:
[0050] Table 1 Vermiculite membrane mechanical properties test data
[0051] Embodiment 2 Embodiment 1 Embodiment 3 Tensile strain 2.1% 1.7% 1.1% toughness <![CDATA[1.9MJ / m 3 ]]> <![CDATA[1.45MJ / m 3 ]]> <![CDATA[0.9MJ / m 3 ]]> Tensile Strength 14.2MPa 15.8MPa 17.3MPa
[0052] Table 2 Mechanical properties test data of thermal expansion vermiculite paper
[0053] Embodiment 2 Embodiment 1 Embodiment 3 Tensile strain 7.9% 6.1% 4.2% toughness <![CDATA[5.4MJ / m 3 ]]> <![CDATA[3.6MJ / m 3 ]]> <![CDATA[1.9MJ / m 3 ]]> Tensile Strength 10.1MPa 11.5MPa 13.2MPa
[0054] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0055] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing nano-laminated thermal expansion vermiculite paper, characterized in that: The following steps are involved: Step S1: weighing the following raw materials according to mass fractions: 0.1-1 parts of oxalic acid powder, 1-2 parts of heat-expanded vermiculite powder, 5-10 parts of deionized water, and 5-30 parts of micron-sized ceramic balls; Step S2: dissolving the oxalic acid powder and the heat-expanded vermiculite powder in deionized water, and mixing to obtain a heat-expanded vermiculite suspension; Step S3: adding micron-sized ceramic balls to the heat-expanded vermiculite suspension obtained in step S2, and then stirring for 6-10 hours, wherein the micron-sized ceramic balls shear the heat-expanded vermiculite and drive the vermiculite particles in the heat-expanded vermiculite to shear and rub against each other, thereby peeling the vermiculite nanosheets from the surface of the vermiculite particles to obtain a vermiculite nanosheet paste; Step S4: pouring the vermiculite nanosheet paste obtained in step S3 into a circular polytetrafluoroethylene mold and fully drying it to obtain a vermiculite film; Step S5: treating the vermiculite film obtained in step S4 at high temperature, the oxalic acid molecules between the vermiculite nanosheets are instantly decomposed into gas, and the water molecules between the vermiculite nanosheets are instantly vaporized, and the vermiculite film expands to obtain thermal expansion vermiculite paper.
2. The method for preparing a nano-laminated thermal expansion vermiculite paper according to claim 1, characterized in that: In step S1, the bulk density of the heat-expanded vermiculite powder is 0.07-0.29 g / cm 3 The micron-sized ceramic balls include zirconium oxide, aluminum oxide or silicon nitride micron-sized balls, and the diameter of the micron-sized ceramic balls is 200-800 μm.
3. The method for preparing a nano-laminated thermal expansion vermiculite paper according to claim 2, characterized in that: In step S3, the stirring linear speed is 10m / s-25m / s, the thickness of the vermiculite nanosheets is less than 5nm, the size of the vermiculite nanosheets is 50-800μm, and the viscosity of the vermiculite nanosheet paste is 300-600pa·s.
4. The method for preparing a nano-laminated thermal expansion vermiculite paper according to claim 3, characterized in that: In step S4, the drying temperature is 50-80° C., the drying time is 2-5 hours, and the thickness of the vermiculite film is 5-20 μm.
5. The method for preparing a nano-laminated thermal expansion vermiculite paper according to claim 4, characterized in that: In step S5, the high temperature treatment temperature is 300-600° C., and the treatment time is 2-10 minutes.
Citation Information
Patent Citations
Preparation method of inorganic vermiculite film
CN102070154A
Graphene and fabrication method thereof and super capacitor
CN103011143A
Preparation method of graphene
CN103991868A
Vermiculite nanosheet, preparation method and production system thereof and vermiculite nanosheet heat stabilizer
CN116715248A
Vermiculite nanosheet composite film and preparation method thereof
CN118320642A